Mechanism underlying sevoflurane-induced protection in cerebral ischemia–reperfusion injury - Chen Bing (De Gruyter, 2021)
Cerebral ischemia is an extremely complex disease that can be caused by a variety of factors. Cerebral ischemia can cause great harm to human body. Sevoflurane is a volatile anesthetic that is frequently used in clinic, and has a lot of advantages, such as quick induction of general anesthesia, quick anesthesia recovery, no respiratory tract irritation, muscle relaxation, and small cycle effect. The mechanism of sevoflurane preconditioning or post-treatment induction is poorly understood. The purpose of this study was to illustrate the mechanism underlying sevoflurane-induced protection in cerebral ischemia–reperfusion injury and also provide theoretical guidance for future research.